Occult hepatitis B virus infection in people with haemophilia in South Africa - Kgotleng O; Msomi N; Mthethwa LD; Potgieter J; Mahlangu JN; Karodia M; Ntabeni NL (The Journal of Haemophilia Practice, 2025)
Occult hepatitis B virus (HBV) infection (OBI) is defined as the presence of HBV DNA in the absence of HBV surface antigen (HBsAg) serological markers. Despite the high prevalence of HBV infection in many communities, OBI prevalence among people with haemophilia (PWH) remains poorly characterised in South Africa.